NEW ISSUES OF ATP SYSTEMS IN A SUPPLY CHAIN (Literature Review) - Tanti Octavia (Institute of Research and Community Outreach - Petra Christian University, 2004)
This paper discusses the concept of studies an Available to Promise (ATP) system by looking beyond what traditionally highlighted in literature concerning Supply Chain. Advanced ATP systems are implemented in practice depends on the company's strategy. However, The performance measures of ATP system become very important and more complex in order to measure the efficiency and effectiveness of ATP system in a supply chain. This paper concludes seven factors influence ATP system in a supply chain.